A helicase-containing module defines a family of pCD630-like plasmids in Clostridium difficile. (February 2018) - Smits, Wiep Klaas; Weese, J. Scott; Roberts, Adam P.; Harmanus, Céline; Hornung, Bastian
Abstract: Clostridium difficile is a Gram-positive and sporulating enteropathogen that is a major cause of healthcare-associated infections. Even though a large number of genomes of this species have been sequenced, only a few plasmids have been described in the literature. Here, we use a combination of in silico analyses and laboratory experiments to show that plasmids are common in C. difficile . We focus on a group of plasmids that share similarity with the plasmid pCD630, from the reference strain 630. The family of pCD630-like plasmids is defined by the presence of a conserved putative helicase that is likely part of the plasmid replicon. This replicon is compatible with at least some other C. difficile replicons, as strains can carry pCD630-like plasmids in addition to other plasmids. We find two distinct sub-groups of pCD630-like plasmids that differ in size and accessory modules. This study is the first to describe a family of plasmids in C. difficile . Highlights: pCD630 is a member of a larger family of plasmids. The family is defined by a conserved helicase and is modular. pCD630-like plasmids are common in diverse C. difficile strains. pCD630 is not present in all strains derived from the reference strain 630.